Rubber composite material, rubber compound and preparation method thereof

By modifying the coupling agent of the carbon black and mixing it with natural latex, wet mixing technology is used to prepare rubber composite materials, which solves the high rolling resistance and dust pollution of the carbon black filling material in the tire tread glue, and achieves high The combination of wear resistance and low energy consumption has significantly improved the comprehensive performance of rubber composite materials.

CN119320519AInactive Publication Date: 2025-01-17QINGDAO HEIMAO NEW MATERIAL RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411363048.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The rubber composite materials filled with carbon black in the existing tire tread rubber have high rolling resistance and dust pollution problems. The traditional mixing technology consumes a lot of energy and uneven dispersion of fillers, making it difficult to have high wear resistance and low heat generation performance.

Method used

Coupling agent is used to modify the carbon black to form a carbon black slurry mixed with natural latex. After flocculation and dehydration, a rubber composite material with low energy consumption and high dispersion is prepared, and the energy consumption and the Dust pollution enhances the interface interaction between carbon black and rubber, and improves the comprehensive performance of rubber.

Benefits of technology

It effectively reduces the energy consumption and dust pollution in the carbon black mixing process, improves the wear resistance and low rolling resistance of rubber, and controls the stability of product quality, significantly improving the comprehensive performance of rubber composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a rubber composite material, a rubber compound and a preparation method thereof, and the method comprises the following steps: (1) modifying carbon black by using a coupling agent to obtain carbon black slurry; (2) mixing the carbon black slurry and natural latex to obtain a natural latex / carbon black mixed solution; and (3) flocculating the natural latex / carbon black mixed solution, filtering, and drying to obtain the rubber composite material. The rubber composite material prepared by the method disclosed by the invention has higher wear resistance, and the heat generation and rolling resistance of rubber are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tires, and in particular to a rubber composite material, a rubber compound and a preparation method thereof. Background Art

[0002] With the development and progress of electric vehicles and autonomous driving technology, the comprehensive performance of corresponding tires has gradually improved, including improving fuel efficiency, reducing fuel consumption, reducing automobile exhaust emissions, etc. In addition, tires are also required to have higher wear resistance, lower rolling resistance and lower noise.

[0003] Carbon black is one of the most widely used reinforcing fillers. It is widely used because the filled rubber composites prepared by it have higher wear resistance when used in tire tread rubber. However, compared with silica, the rolling resistance of carbon black is significantly higher.

[0004] Therefore, developing carbon black-filled rubber composite materials with low heat generation performance so that they can maintain high wear resistance while also having low heat generation performance is an urgent problem to be solved. Summary of the invention

[0005] The conventional rubber mixing technology has the problems of serious filler flying, high mixing energy consumption, and uneven filler dispersion. The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a rubber composite material, a mixed rubber and a preparation method thereof.

[0006] In a first aspect of the present invention, the present invention provides a method for preparing a rubber composite material. According to a specific embodiment of the present invention, the method comprises:

[0007] (1) modifying carbon black with a coupling agent to obtain a carbon black slurry;

[0008] (2) mixing the carbon black slurry and natural rubber latex to obtain a natural rubber latex / carbon black mixed solution;

[0009] (3) flocculating, dehydrating, and then drying the natural rubber latex / carbon black mixed solution to obtain a rubber composite material.

[0010] In a second aspect of the present invention, the present invention provides a rubber composite material, which is prepared by the method described in the first aspect of the present invention.

[0011] In a third aspect of the present invention, the present invention provides a rubber compound including the rubber composite material described in the second aspect of the present invention.

[0012] Beneficial effects of the present invention:

[0013] (1) Reduce energy consumption: By adopting wet mixing technology, the energy consumption in the mixing process of carbon black and rubber can be effectively reduced. Compared with the existing mixing process, the energy consumption is reduced by more than 30%, which is conducive to reducing production costs and carbon emissions, and meets the current environmental protection requirements;

[0014] (2) Improve dust pollution: By mixing carbon black aqueous dispersion with natural rubber latex, the dust of carbon black mixed into rubber can be greatly reduced, thereby preventing mixing workers from inhaling dust and ensuring their health; at the same time, avoiding the use of dust suppressants will not affect the performance of rubber;

[0015] (3) Improve the comprehensive performance of rubber: Through the surface modification technology of carbon black coupling agent, the interfacial interaction between carbon black and rubber can be enhanced, the dispersion effect of carbon black can be improved, and thus the comprehensive performance of rubber can be improved. Compared with the existing wet mixing technology, the pre-modified carbon black has a stronger interfacial bonding effect with natural rubber due to the reactive functional groups of the coupling agent grafted on the surface. It can not only improve the dispersion effect of carbon black in rubber, thereby improving the wear resistance of rubber, reducing the heat generation and rolling resistance of rubber, but also control the modification process to ensure stable product quality.

[0016] (4) Compared with the rubber composite material obtained by dry mixing of the same type and amount of carbon black and the rubber composite material obtained by wet mixing of the same type and amount of carbon black modified by a general coupling agent, the rubber composite material of the present invention has higher wear performance and more obvious advantages in low hysteresis performance. This is because the coupling agent modification process used in the present invention chemically connects the carbon black and the natural rubber, so that the interaction between the carbon black and the rubber is significantly enhanced, and the Payne effect of the carbon black-filled rubber is significantly reduced.

[0017] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0018] The following detailed description of embodiments of the present invention is intended to be used to explain the present invention, but cannot be construed as limiting the present invention. The following embodiments are exemplary and are intended to be used to explain the present invention, but cannot be construed as limiting the present invention.

[0019] In a first aspect of the present invention, the present invention provides a method for preparing a rubber composite material. According to a specific embodiment of the present invention, the method comprises:

[0020] S100: Modification of carbon black using coupling agents

[0021] In this step, the carbon black is modified with a coupling agent to obtain a carbon black slurry. The inventors have found that by pre-modifying the carbon black with a coupling agent to obtain coupling agent-modified carbon black, the modified carbon black has better compatibility with the rubber matrix than the unmodified carbon black, so that the rubber composite material has better comprehensive performance.

[0022] In some embodiments, the coupling agent, carbon black and water are mixed to obtain a carbon black slurry.

[0023] In some embodiments, the mass ratio of the carbon black, the coupling agent and the water is 1:(0.01-0.1):(10-100).

[0024] In some embodiments, the carbon black includes one or more of N134, N115, N121, N234, N220, N339, N326, N375, or N347.

[0025] In some embodiments, the coupling agent includes one or more of 2,6-dihydroxybenzoic acid hydrazide, alkanolamide (ALK), nitrosoaniline, dinitrodiamine compounds, 4,4'-dithiodiphenylamine, and isopropyl tri(dodecylbenzenesulfonyl) titanate.

[0026] In some preferred embodiments, when the coupling agent is in a solid state, the solid coupling agent and carbon black are pre-dry ball-milled, wet granulated and dried in sequence to obtain solid coupling agent-modified carbon black, and then the solid coupling agent-modified carbon black and water are mixed to obtain carbon black slurry.

[0027] Specifically, the rotation speed of the above-mentioned dry ball milling is 100-500rpm, and the time is 0.1-5h; the mass ratio of the granulation liquid and the coupling agent in the wet granulation process is (90-100): (1-10); the drying temperature is 300-800°C, and the modified carbon black is dried until the moisture content is no more than 1wt%.

[0028] In some embodiments, the mixing method of the coupling agent, carbon black and water, and the mixing method of the solid coupling agent modified carbon black and water are not particularly limited, and include one or more of ball milling, stirring, emulsification or impact milling. For example, the speed of ball milling is 100-500 rpm, and the time is 0.1-5h; the speed of stirring is 800-2000 rpm, and the time is 10-90min; the speed of emulsification is 5000-12000 rpm, and the time is 5-30min; the frequency of impact milling is 12-30Hz, and the time is 10-100min.

[0029] S200: Mixing carbon black slurry and natural rubber latex

[0030] In this step, the carbon black slurry and natural rubber latex are mixed to obtain a natural rubber latex / carbon black mixed solution.

[0031] In some embodiments, the mass ratio of the carbon black slurry to the natural rubber latex is 1:(1-3).

[0032] In some embodiments, the dry rubber content in the natural rubber latex is 10 to 60 wt %.

[0033] It should be noted that the method of mixing the carbon black slurry and natural rubber latex is not particularly limited, and includes one or more of ball milling, stirring, emulsification or impact milling. For example, the speed of the ball milling is 100-500 rpm, and the time is 0.1-5 hours; the speed of the stirring is 800-2000 rpm, and the time is 10-90 minutes; the speed of the emulsification is 5000-12000 rpm, and the time is 5-30 minutes; the frequency of the impact milling is 12-30 Hz, and the time is 10-100 minutes.

[0034] S300: flocculating the natural rubber latex / carbon black mixed solution, filtering and drying

[0035] In this step, the natural latex / carbon black mixed solution is mixed with a flocculant to perform flocculation, and the flocculated and coprecipitated rubber composite material is filtered, dehydrated and dried to obtain a rubber composite material. By mixing carbon black with water to form a carbon black slurry, and then mixing the carbon black slurry with natural latex, the heat generation, energy consumption and dust pollution of the rubber can be greatly reduced. This is because during the wet mixing process, the carbon black is dispersed in the water, which avoids the flying dispersion and high-intensity shearing of the carbon black during the dry mixing process, thereby reducing the mixing energy consumption and dust pollution.

[0036] Specifically, a forced air drying oven and / or a vacuum drying oven may be used for dehydration to constant weight. This process can reduce the water content and avoid condensation. The drying temperature is 125-250°C.

[0037] In some embodiments, the mass ratio of the natural rubber latex / carbon black mixture to the flocculant is (90-99):(1-10).

[0038] In some embodiments, the flocculant used in the flocculation includes one or more of calcium chloride, ethanol and glacial acetic acid.

[0039] In some embodiments, the flocculation time is 0.1 to 5 hours.

[0040] In a second aspect of the present invention, the present invention provides a rubber composite material, which is prepared by the method described in the first aspect of the present invention.

[0041] It should be noted that the features and advantages described above for the method for preparing the rubber composite material are also applicable to the rubber composite material, and will not be described in detail herein.

[0042] In a third aspect of the present invention, the present invention provides a rubber compound including the rubber composite material described in the second aspect of the present invention.

[0043] It should be noted that the features and advantages described above for the rubber composite material and the preparation method thereof are also applicable to the rubber mix, and will not be described in detail here.

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Unless otherwise specified, the preparation processes in the following examples and comparative examples are all conventional means in the prior art, and the raw materials or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Therefore, no further description is given.

[0046] Example 1

[0047] (1) 1.26 g of alkanolamide, 42 g of carbon black N234 and 420 g of water were wet ball milled at 300 rpm for 30 min to obtain a carbon black slurry;

[0048] (2) adding 500 g of natural rubber latex (with a dry rubber content of 20 wt%) to the carbon black slurry of step 1, and wet-milling at 200 rpm for 30 min to obtain a natural rubber latex / carbon black mixed solution;

[0049] (3) Add 10 g of flocculant CaCl2 to the above natural rubber latex / carbon black mixture and flocculate for 10 min. After filtering out the liquid, place it in a forced air drying oven and a vacuum drying oven to dry to constant weight to obtain wet composite rubber SF-1.

[0050] 142 parts of wet composite rubber SF-1, other components are: 4 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4020, sulfur and accelerator: 1.5 parts of accelerator CZ, 1.5 parts of sulfur. The process is: first add 142 parts of wet composite rubber SF-1 to the internal mixer for blending, then add other components to the internal mixer for blending, then heat to 145-155°C, mix at constant temperature for 5 minutes, cool to room temperature after the rubber is discharged, and then add sulfur and accelerator on the open mill to prepare the mixed rubber. Vulcanize on a flat vulcanizer at 150°C and a pressure of 15MPa for the positive vulcanization time. Finally, the physical and mechanical properties and dynamic mechanical properties of the vulcanized rubber are tested.

[0051] Example 2

[0052] (1) 4.2 g of 2,6-dihydroxybenzoyl hydrazide and 50 g of carbon black N234 were dry-milled at 300 rpm for 30 min, and then 150 g of water was added for wet granulation, and the mixture was dried in a drying oven at 200° C. to obtain coupling agent-modified carbon black G234; then the coupling agent-modified carbon black G234 and 500 g of water were wet-milled at 200 rpm for 30 min to obtain a carbon black slurry;

[0053] (2) adding 600 g of natural rubber latex (with a dry rubber content of 16.7 wt%) to the carbon black slurry of step 1, and wet-milling at 200 rpm for 30 min to obtain a natural rubber latex / carbon black mixed solution;

[0054] (3) Add 20 g of flocculant CaCl2 to the natural rubber latex / carbon black mixture and flocculate for 0.2 h. After filtering out the liquid, place it in a forced air drying oven and a vacuum drying oven to dry to constant weight to obtain wet composite rubber SF-2.

[0055] 150 parts of wet composite rubber SF-2, other components are: 4 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4020, sulfur and accelerator: 1.5 parts of accelerator CZ, 1.5 parts of sulfur. The process is: first add 150 parts of wet composite rubber SF-2 to the internal mixer for blending, then add other components to the internal mixer for blending, then heat to 145-155°C, mix at constant temperature for 5 minutes, cool to room temperature after the rubber is discharged, and then add sulfur and accelerator on the open mill to prepare the mixed rubber. Vulcanize on a flat vulcanizer at 150°C and a pressure of 15MPa for the positive vulcanization time. Finally, the physical and mechanical properties and dynamic mechanical properties of the vulcanized rubber are tested.

[0056] Example 3

[0057] (1) 42 g of carbon black N234, 2.2 g of isopropyl tri(dodecylbenzenesulfonyl) titanate and 420 mL of water were mixed and stirred at 1000 rpm for 30 minutes at 25° C. using a high-speed stirrer to form a carbon black slurry;

[0058] (2) adding 500 g of natural rubber latex (with a dry rubber content of 20 wt%) to the carbon black slurry in step 1 and stirring, and then continuing wet ball milling at 1000 rpm for 60 min to obtain a natural rubber latex / carbon black mixed solution;

[0059] (3) Add 20 g of flocculant CaCl2 to the natural rubber latex / carbon black mixture and flocculate for 0.5 h. After filtering out the liquid, place it in a forced air drying oven and a vacuum drying oven to dry to constant weight to obtain wet composite rubber SF-3.

[0060] 142 parts of wet composite rubber SF-3, rubber processing aids are: 4 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4020, sulfur and accelerator: 1.5 parts of accelerator CZ, 1.5 parts of sulfur. The process is: first add 142 parts of wet composite rubber SF-2 to the internal mixer for blending, then add other components to the internal mixer for blending, then heat to 145-155°C, mix at constant temperature for 5 minutes, cool to room temperature after the rubber is discharged, and then add sulfur and accelerator on the open mill to prepare the mixed rubber. Vulcanize on a flat vulcanizer at 150°C and a pressure of 15MPa for the positive vulcanization time. Finally, the physical and mechanical properties and dynamic mechanical properties of the vulcanized rubber are tested.

[0061] Comparative Example 1

[0062] 100 parts of natural rubber NR, 42 parts of carbon black N234, 1.26 parts of coupling agent alkanolamide, other components are: 4 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4020, sulfur and accelerator: 1.5 parts of accelerator CZ, 1.5 parts of sulfur. The process is: first add 100 parts of natural rubber to the internal mixer for blending, then evenly mix carbon black N234 and coupling agent alkanolamide and divide them into two equal parts, add them to the internal mixer in turn for blending, then add rubber processing aids to the internal mixer for blending, then heat to 145-155℃, mix at constant temperature for 5 minutes, cool the rubber to room temperature after draining, add sulfur and accelerator to the open mill for blending to prepare the mixed rubber. Vulcanize on a flat vulcanizer at 150℃ and pressure of 15MPa for the positive vulcanization time. Finally, test the physical and mechanical properties and dynamic mechanical properties of the vulcanized rubber.

[0063] Comparative Example 2

[0064] 100 parts of natural rubber NR, 50 parts of carbon black N234, 4.2 parts of coupling agent 2,6-dihydroxybenzoic acid hydrazide, other components are: 4 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4020, sulfur and accelerator: 1.5 parts of accelerator CZ, 1.5 parts of sulfur. The process is: first add 100 parts of natural rubber to the internal mixer for blending, then evenly mix carbon black N234 and coupling agent 2,6-dihydroxybenzoic acid hydrazide and divide into two equal parts, add them to the internal mixer in turn for blending, then add rubber processing aids to the internal mixer for blending, then heat to 145-155℃, mix at constant temperature for 5 minutes, cool to room temperature after rubber discharge, add sulfur and accelerator on the open mill for blending to prepare the mixed rubber. Vulcanize on a flat vulcanizer at 150℃ and pressure of 15MPa, and the time is the positive vulcanization time. Finally, the physical and mechanical properties and dynamic mechanical properties of the vulcanized rubber were tested.

[0065] Comparative Example 3

[0066] 100 parts of natural rubber NR, 42 parts of carbon black N234, 2.2 parts of coupling agent isopropyl tri (dodecylbenzene sulfonyl) titanate, other components are: 4 parts of zinc oxide, 2 parts of stearic acid, 1.5 parts of antioxidant RD, 1.5 parts of antioxidant 4020, sulfur and accelerator: 1.5 parts of accelerator CZ, 1.5 parts of sulfur. The process is: first add 100 parts of natural rubber to the internal mixer for blending, then evenly mix carbon black N234 and coupling agent isopropyl tri (dodecylbenzene sulfonyl) titanate and divide into two equal parts, add them to the internal mixer in turn for blending, then add rubber processing aids to the internal mixer for blending, then heat to 145-155°C, mix at constant temperature for 5 minutes, cool the rubber to room temperature, add sulfur and accelerator on the open mixer for blending to prepare the mixed rubber. Vulcanization was carried out on a flat vulcanizing machine at 150°C and a pressure of 15 MPa for the positive vulcanization time. Finally, the physical and mechanical properties and dynamic mechanical properties of the vulcanized rubber were tested.

[0067] Comparative Example 4

[0068] No coupling agent was added, and the rest was the same as in Example 1.

[0069] Comparative Example 5

[0070] The alkanolamide in Example 1 was replaced by an equal amount of γ-aminopropyltriethoxysilane coupling agent (KH550), and the rest was the same as Example 1.

[0071] The performance of the mixed rubber obtained in each embodiment and comparative example was tested by the following method. The test results are shown in Table 1 below:

[0072] (1) RPA: Storage modulus difference ΔG' = G'@0.28% - G'@42%, ASTM D8059-16 Standard test method for dynamic strain softening (Payne effect) of uncured rubber compounds using a sealed chamber rotorless shear rheometer;

[0073] RPA is the storage modulus of the rubber compound at 1.0% shear strain, which is used to study the Payne effect of carbon black / rubber compounds. A small value indicates good dispersion of carbon black.

[0074] (2) Hardness: GBT 531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore hardness method (Shore hardness);

[0075] (3) 300% elongation stress: GBT 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;

[0076] The higher the hardness and 300% modulus of elongation of the vulcanized rubber, the less carbon black aggregates there are in the rubber matrix, which reduces the area of ​​stress concentration and improves the reinforcing effect of carbon black on the rubber. The stronger the filler-rubber interaction is; (4) DIN wear volume: GBT 9867-2008 Determination of the wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrader method). The larger the wear volume, the worse the wear resistance of the vulcanized rubber.

[0077] The addition of inorganic fillers such as carbon black can significantly increase the density and hardness of natural rubber, reduce the friction coefficient of the composite material, and reduce the degree of adhesive friction. Therefore, the hardness of the material is increased, the tendency of adhesive friction is weakened, and the wear resistance of the rubber composite material is improved.

[0078] (5) Compression heat generation: GB_T 1687.3-2016 Determination of temperature rise and fatigue resistance of vulcanized rubber in flexure test Part 3: Compression flexure test (constant strain type)

[0079] Its value is directly related to the mutual friction between all components of the carbon black / rubber composite material. The smaller the value, the stronger the interaction between the filler and the rubber, the smaller the filler-filler friction, and the lower the dynamic heat generation of the rubber composite material.

[0080] (6) Rebound: GBT 1681-2009 Determination of the rebound elasticity of vulcanized rubber.

[0081] The larger the value, the higher the elasticity of the rubber.

[0082] Table 1 Main physical and mechanical properties and dynamic properties of vulcanized rubber

[0083]

[0084] As shown in Table 1, Example 1 vs. Comparative Example 1, Example 2 vs. Comparative Example 2, Example 3 vs. Comparative Example 3, it is found that compared with the rubber prepared by the dry mixing technology of ordinary carbon black and the rubber prepared by the wet mixing technology of carbon black surface-modified by coupling agent, the rubber prepared by the method of the present invention has a weaker Payne effect. This is because the wet mixing technology pre-shears or ball-mills the carbon black at high speed, breaks the agglomeration of the carbon black, weakens the filler network of the carbon black, achieves a more uniform mixing with the natural latex, and improves the dispersion of the carbon black in the rubber matrix, thereby giving the rubber composite material lower compression heat generation and higher rebound.

[0085] By comparing Example 1 with Comparative Examples 4 and 5, it is found that the wet-process rubber prepared by the coupling agent-modified carbon black used in the present invention has higher hardness and 300% modulus of tensile stress, lower hysteresis performance and better wear resistance than the wet-process rubber prepared by using general coupling agent-modified carbon black or carbon black not modified by coupling agent; this is because the chemical connection between carbon black and rubber macromolecules is achieved through modification, and the interfacial bonding effect between carbon black and rubber is further strengthened, thereby improving the hardness and modulus of tensile stress of rubber; the compression heat generation is lower, the rebound is higher, and the wear volume is lower, indicating that the coupling agent-modified carbon black used in the present invention can improve the dispersibility of carbon black in the rubber material, and form a chemical interface between carbon black and rubber, and the rubber molecular chain enters the carbon black filler network to form an interpenetrating network structure, thereby improving the reinforcing effect of carbon black on rubber, increasing the crosslinking degree of the vulcanized rubber, increasing the tensile strength, and improving the dynamic mechanical properties of the rubber.

[0086] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0087] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a rubber composite material, characterized in that: The method comprises: (1) modifying carbon black with a coupling agent to obtain a carbon black slurry; (2) mixing the carbon black slurry and natural rubber latex to obtain a natural rubber latex / carbon black mixed solution; (3) flocculating the natural rubber latex / carbon black mixed solution, filtering and drying to obtain a rubber composite material.

2. The method according to claim 1, characterized in that In step (1), the carbon black, the coupling agent and water are mixed to obtain a carbon black slurry; and / or, The mass ratio of the carbon black, the coupling agent and the water is 1:(0.01-0.1):(10-100).

3. The method according to claim 1, characterized in that In step (1), a solid coupling agent and carbon black are sequentially subjected to dry ball milling, wet granulation and drying to obtain solid coupling agent modified carbon black, and then the solid coupling agent modified carbon black is mixed with water to obtain the carbon black slurry; and / or, The dry ball milling has a rotation speed of 100 to 500 rpm and a time of 0.1 to 2 hours; and / or, The mass ratio of the granulation liquid to the coupling agent during the wet granulation process is (90-100): (1-10).

4. The method according to any one of claims 1 to 3, characterized in that: The mixing method includes one or more of ball milling, stirring, emulsification or impact milling; and / or, The ball milling speed is 100-500 rpm, and the time is 0.1-2 h; and / or, The stirring speed is 800-2000 rpm and the stirring time is 10-90 min; and / or, The emulsification frequency is 5000-12000 rpm, and the time is 5-30 min; and / or, The frequency of the impact mill is 12-30 Hz, and the time is 10-100 min.

5. The method according to claim 1, characterized in that In step (1), the carbon black includes one or more of N134, N115, N121, N234, N220, N339, N326, N375 or N347; and / or, The coupling agent includes one or more of 2,6-dihydroxybenzoic acid hydrazide, alkanolamide (ALK), nitrosoaniline, dinitrodiamine compound, 4,4'-dithiodiphenylamine, and isopropyl tri(dodecylbenzenesulfonyl) titanate.

6. The method according to claim 1, characterized in that In step (2), the mass ratio of the carbon black slurry to the natural rubber latex is 1:(1-3); and / or, The dry rubber content in the natural rubber latex is 10-60wt%.

7. The method according to claim 1, characterized in that In step (3), the flocculant used for flocculation includes one or more of calcium chloride, ethanol and glacial acetic acid; and / or, The mass ratio of the natural latex / carbon black mixed liquid to the flocculant is (90-99):(1-10).

8. A rubber composite material, characterized in that: The rubber composite material is prepared by the method according to any one of claims 1 to 7.

9. A rubber mix, characterized in that: The rubber mix comprises the rubber composite material as claimed in claim 8.

Citation Information

Patent Citations

  • Rubber composition and tire using the same

    CN103403080A

  • High-wear-resistance and low-heat-generation carbon black masterbatch and preparation method thereof

    CN113861526A

  • White-carbon-black-containing wet-process mixed masterbatch suitable for tire tread rubber, preparation method of white-carbon-black-containing wet-process mixed masterbatch and rubber composition

    CN115572418A

  • Preparation method and application of coupling modified carbon black for plastics

    CN117801573A

  • Wet mixing method of cracked carbon black / natural rubber composite material

    CN118580579A